2014
DOI: 10.1016/j.ecoenv.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid assisted phytoremediation of cadmium by Brassica napus L

Abstract: Phytoextraction is an eco-friendly and cost-effective technique for removal of toxins, especially heavy metals and metalloids from contaminated soils by the roots of high biomass producing plant species with subsequent transport to aerial parts. Lower metal bioavailability often limits the phytoextraction. Organic chelators can help to improve this biological technique by increasing metal solubility. The aim of the present study was to investigate the possibility of improving the phytoextraction of Cd by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
125
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(144 citation statements)
references
References 42 publications
18
125
1
Order By: Relevance
“…These findings are similar to other studies in which increased root or short biomass was observed after CA or microorganism-assisted phytoextraction (Najeeb et al 2009;Khan et al 2015). The enhanced biomass may be related to the enhanced antioxidant enzyme activity of plants, which decreases the production of H 2 O 2 and electrolyte leakage (Ehsan et al 2014). However, Pb concentration in S. nigrum was considerably lower than that in soil.…”
Section: Discussionsupporting
confidence: 77%
“…These findings are similar to other studies in which increased root or short biomass was observed after CA or microorganism-assisted phytoextraction (Najeeb et al 2009;Khan et al 2015). The enhanced biomass may be related to the enhanced antioxidant enzyme activity of plants, which decreases the production of H 2 O 2 and electrolyte leakage (Ehsan et al 2014). However, Pb concentration in S. nigrum was considerably lower than that in soil.…”
Section: Discussionsupporting
confidence: 77%
“…Phytoextraction uses high biomass producing plants to remove toxicants from soil by accumulating them in harvestable tissues such as stems and leaves (Pilon-Smits 2005;Shakoor et al 2013). However, efficiency of plants to uptake toxic metals varies with soil type, plant species, and environmental conditions (Metwally et al 2005;Jadia and Fulekar 2008;Yang et al 2010;Ehsan et al 2014). Various plant species, known as hyperaccumulators, have been used for the phytoremediation of metal-contaminated soils.…”
Section: Introductionmentioning
confidence: 98%
“…However, the pre-incubation of plants with citrate showed doubled absorption of Cd and a 5-8 times increase in the concentration of Cd in xylem exudate, where at least a portion of the Cd was present as a complex with citrate (Senden, Van Paassen, Van der Meer, and Wolterbeek, 1995). In a study on Brassica napus plants in water culture, it was found that citrate application at a concentration of 2.5 mM in medium containing 10 or 50 µm Cd contributed to the 1.5-times increase in the accumulation of Cd in roots, stems, and leaves of canola (Ehsan et al, 2014). Stimulation of Cd accumulation under the effect of exogenous citrate (but not tartrate) was shown for Cd/Zn hyperaccumulator Sedum alfredii (Lu et al, 2013) and for Spinacia oleracea plants (Degryse, Smolders, and Parker, 2006).…”
Section: Plant Sciencementioning
confidence: 99%
“…However, some authors do not exclude the possibility of metals uptake in chelated form, with the participation of ligands carriers (Degryse, Smolders, and Parker, 2006;Lux, Martinka, Vaculik, and White, 2011) or through the apoplast in root tips where Casparian strips are not fully formed, or directly into the xylem vessels in case the integrity of membranes is disrupted after exposure to chelators (Evangelou, Ebel, and Schaeffer, 2007). At the same time, it should be noted that exogenous application of organic acids is carried out directly in the form of acids, while the root secretion of acids is in the form of anions and can be accompanied by secretion of K + , so there is no strong acidification of the media (Ryan, Delhaize, and Jones, 2001;Kochian, Pineros, Liu, and Magalhaes, 2015) Analyzing the possible mechanism of the stimulating effect of citrate and other exogenously applied acids on the bioavailability of metals in soil, the authors explain it mainly through the acidification of the environment, contributing to desorption of metals from the solid phase of the soil, the complexation of metals with anions of acids and their conversion into a more mobile, soluble chelated form (Panfili et al, 2009;Ehsan et al, 2014). The most important factor stimulating the absorption of Cd by plants, according to Panfili et al (2009), is higher lability of the Cd chelate complex compared to Cd 2+ ions, thus providing Cd concentration at the root surface.…”
Section: Plant Sciencementioning
confidence: 99%